ANALISIS BEBAN KERJA FISIK DAN MENTAL PEKERJA PADA PROSES VULKANISIR BAN DENGAN MENGGUNAKAN METODE CARDIOVASCULAR LOAD (CVL) DAN NASA-TLX - Joko Susetyo; Turnip, Renaldi; Wisnubroto, Petrus (Jurnal Rekavasi, 2022)
UD. Pandawa Tire is a UD engaged in the manufacture of tires retreaded. The production process at Pandawa Tires still often does overtime due to the number of new employees 9 people and the average target of making 60 tires every day which causes fatigue and mental and physical workload. The analytical methods used to measure the physical and mental workload of workers are Cardiovascular Load (CVL) and the National Aeronautics and Space Administration Task Load Index (NASA-TLX). The results showed that the greatest physical workload was felt by workers with a CVL percentage of 46.1%, which was between 30% to 60% in the medium category, meaning that improvements are needed but not urgent. While the results of the measurement of mental workload showed that all workers were included in the high category, with the largest NASA-TLX score of 83.33. Correlation Test was Pearson Product Moment conducted to see the relationship between the value of the physical and mental workload received by the worker. The results of the calculation of the correlation test show that there is a relationship between CVL and NASA-TLX, although there is a correlation, but the correlation is significant in influencing each other between the amount of physical workload and mental workload felt by workers. The correlation value of r obtained is 0.672. Which means that there is a strong positive correlation between the physical workload and the mental burden felt by the Pandawa tire workers